Hubungan Riwayat Merokok Dengan Nilai Ankle Brachial Index di Wilayah Kerja Puskesmas Gribig Kota Malang - Desyati, Fanda Eka; Tyas, Maria Diah Ciptaning; Lundy, Fiashriel (Jurnal Keperawatan Terapan; Vol 8 No 1 (2022): Jurnal Keperawatan Terapan (E-Journal)DO - 10.31290/jkt.v8i1.1860, 2022)
Smoking is something we often encounter in society and has become part of most people's routine activities. In cigarettes, there are compounds that can worsen the condition of blood vessels and blood flow which are obtained by measuring the Ankle Brachial Index (ABI) which is the ratio of systolic blood pressure in the arm to systolic pressure in the lower leg. This study aims to analyze the relationship between smoking history and the Ankle Brachial Index (ABI) value. Correlational research design, a sample of 40 respondents using purposive sampling. The research instruments used were interview sheets, measurement observation sheets and standard operating procedures for measuring the ankle brachial index. The data were processed using SPSS 25, with a is 0.05. The results showed that most categories of non smokers got an ABI value more than 1.0 to 1.2 which was categorized as normal vascularity as much as 17.5 percent, the light smoker category mostly got an ABI value more than 1.0-1.2 which was categorized as normal vascularity as much as 15 percent, the smoker category being with an ABI value more than 1.3 to 1.4 is categorized as vascularity, has an elevation of 10 percent and an ABI value more than 1.0 to 1.2 which is categorized as 10 percent normal vascularity, for the heavy smoker category an ABi value more than 1.3 to 1.4 is classified as vascularized as having elevation 15 percent. Based on the Spearmen test, it was found that the value of p is 0.564 more than a is 0.05, so that H1 was rejected. It can be concluded that there is no effect between smoking history and Ankle Brachial Index (ABI) value. It is hoped that in future studies to pay attention to other factors related to the Ankle Brachial Index (ABI) value and the measurement will be carried out using a vascular dopler.